Assessment of whole-body occupational radiation exposure in industrial radiography practices in Bangladesh during 2010-2014 - Mohammad Sohelur Rahman; Aleya Begum; Ashraful Hoque; Rezaul Karim Khan; M.M.M. Siraz (Brazilian Journal of Radiation Sciences, 2016)
Presently, ten industrial radiography facilities are operating in Bangladesh using X-ray or gamma-ray sources. During the last 5-year, 14 industrial radiography facilities were received individual monitoring service using thermoluminescent dosimeters (TLDs) from the Health Physics Division (HPD), Atomic Energy Centre, Dhaka under Bangladesh Atomic Energy Commission. HPD is the only individual monitoring service provider in Bangladesh due to external sources of ionizing radiation. The number of monitored industrial radiography facilities ranged from 7 to 14 while the number of worker ranged from 72 to 133 during the study period.  The annual average effective doses received from external radiation in industrial radiography workers and the distributions of the annual effective doses by dose intervals are presented. The distribution of the occupational doses shows that the majority (about 75 %) of workers received doses below 1 mSv for the last 5-years. Even though, very few workers (about 1%) received doses higher than average annual dose limit (20 mSv), but no workers received doses higher than 100 mSv in 5 consecutive years. The average annual effective dose of industrial radiography workers in Bangladesh is higher than the corresponding values in Tanzania, Greece, Poland, Australia, UK and lower than in Bosnia and Herzegovina, USA and Canada. However, the average annual effective dose is comparable to the corresponding values in China, Brazil, Germany and India. The status and trends in occupational doses show that radiation protection situation at the majority of the workplace were satisfactory. In spite of that, additional measures are required due to big differences observed in the maximum individual doses over the last 5-year.